Have Hungarian districts become more resilient? – A comparison of the 2014 and 2020 Baseline Resilience Indicators for Communities (BRICs) - Csizovszky, Anna (European Journal of Sustainable Development, 2023)
Recent crises have put resilience at the center of sustainability and territorial studies. Enhancing resilience plays a crucial role in sustainable regional development and calls for knowledge of local vulnerabilities as well as capacity for absorption, adaptation, and transformation. Community resilience refers to the ability of different regional levels to adjust their socioeconomic systems to manage the adverse effects of shocks and stresses and to be able to provide adaptive responses. So far, studies have focused mainly on specific areas, which is difficult to apply in the context of successive crises and makes it more challenging to set development priorities. This research adopts the Baseline Resilience Indicators for Communities (BRIC) framework and focuses on changes between 2014 and 2020. The community resilience assessment of Hungarian districts revealed quite a homogenous performance concerning the overall score but showed high heterogeneity concerning the five resilience dimensions evaluated. Over time, the indicators generally increased in the social and economic domains and decreased in the community domain. Besides, rapid suburbanization processes around cities contributed to lower overall performances indicating the necessity of action. Keywords: community resilience, BRIC, regional pattern, Hungary, spatiotemporal analysis